2018
DOI: 10.3390/su10072404
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Effects of Autonomous Driving: A Study on Mobility Preferences in the Future

Abstract: Innovations in the mobility industry such as automated and connected cars could significantly reduce congestion and emissions by allowing the traffic to flow more freely and reducing the number of vehicles according to some researchers. However, the effectiveness of these sustainable product and service innovations is often limited by unexpected changes in consumption: some researchers thus hypothesize that the higher comfort and improved quality of time in driverless cars could lead to an increase in demand f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
82
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 58 publications
(112 reference statements)
2
82
2
4
Order By: Relevance
“…Based on an agent-based simulation model, Martinez, Correia, and Viegas [11] proved that the introduction of a shared-taxi scheme in the city of Lisbon improved the taxi system performance from the users' perspective in a way such that the average waiting time, total travel time, and fare could be reduced. The obtained results further showed that the taxis may also benefit from an increase in operational efficiency which was measured by the average revenue per travelled kilometer [11].The expected dissemination of autonomous vehicles will most likely contribute to the attractiveness of shared mobility services and the efficacy of those systems [12]. Accordingly, the MEGAFON study showed that a combination of a high-performance tramway and a ridepooling system would ensure public mobility in the city of Stuttgart based on a vehicle fleet that includes 7% of today's number of vehicles [13].…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Based on an agent-based simulation model, Martinez, Correia, and Viegas [11] proved that the introduction of a shared-taxi scheme in the city of Lisbon improved the taxi system performance from the users' perspective in a way such that the average waiting time, total travel time, and fare could be reduced. The obtained results further showed that the taxis may also benefit from an increase in operational efficiency which was measured by the average revenue per travelled kilometer [11].The expected dissemination of autonomous vehicles will most likely contribute to the attractiveness of shared mobility services and the efficacy of those systems [12]. Accordingly, the MEGAFON study showed that a combination of a high-performance tramway and a ridepooling system would ensure public mobility in the city of Stuttgart based on a vehicle fleet that includes 7% of today's number of vehicles [13].…”
mentioning
confidence: 77%
“…With the help of intelligent matching algorithms, the routes of passengers who are heading in the same direction are pooled.Ridepooling systems might provide a personalized mobility service on the one hand and ensure the efficiency and sustainability of the transport system on the other hand [8]. Such shared mobility systems might complement public transport [9]; they could also make an important contribution to the improvement of sustainable and livable cities since shared mobility systems might reduce traffic volume and thus decrease CO 2 emissions and the number of parking spaces required [8,[10][11][12][13]. In a simulation study, the International Transport Forum of the Organisation for Economic Co-operation and Development (OECD) revealed that only 2.8% of today's fleet size in the city of Lisbon would be necessary to secure citizens' mobility if shared mobility systems would provide on-demand mobility for citizens [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, findings indicate that the growth of the sharing model will mainly be in public transport. This shows that for the development of sustainable mobility more emphasis should be placed in making public transport more attractive [19]. Another study in France surveyed 425 participants.…”
Section: Autonomous Vehicles (Av) and Their Adoptionmentioning
confidence: 99%
“…It is predicted that in 2030, the majority of vehicles will be classified as Level 2 and Level 4 [15].Despite fast technological development, which drives innovation in the field of AV, user acceptance of automated and autonomous mobility solutions will play a significant role in transportation transformation in the future. Several studies investigated different factors influencing user acceptance of AV from different perspectives [2,4,[17][18][19][20][21][22][23][24][25][26][27]. However, only a few studies have assessed the user perception of AV after the real life experiences [25,27].…”
mentioning
confidence: 99%